Management of pikeperch Sander lucioperca (Linnaeus, 1758) sperm quality after stripping. (11th August 2016) - Schaefer, F. J.; Overton, J. L.; Bossuyt, J.; Żarski, D.; Kloas, W.; Wuertz, S.
Summary: The aim of this study was to identify the potential for optimizing management of sperm quality during commercial reproduction of pikeperch Sander lucioperca . Sperm from different males is often pooled prior to fertilization or stored for short periods (hr) until ovulated eggs become available. A novel approach was applied to assess pooling effects by cross‐wise transfusion of sperm and seminal fluid (SF) of males with differing initial sperm quality. In addition, the effects of two different buffers (glucose and KCl) were tested, as well as a supplementation of melatonin and progesterone (1 mmol L −1 ) to maintain or improve the quality of freshly stripped and incubated (0.5, 1, 2, 4 and 24 hr) sperm. Sperm motility and curvilinear velocity (VCL) were measured by computer assisted sperm analysis (CASA). The VCL proved to be a more sensitive, reliable parameter compared to motility, since significant differences occurred up to 3.5 hr earlier. Transfusion of SF between low and high quality sperm resulted in a significant decrease in sperm with high initial VCL (seven out of 22 transfusions), whereas VCL of low quality sperm could not be improved. In only one case did a transfusion result in an increased VCL. No treatment prevented a significant quality loss over 24 hr or even enhanced sperm performance. Conclusively, pooling sperm of different qualities as well as short‐term storage has a significant, negative impact on overall sperm quality. Pooling should only be considered when the sperm quality is known.